Of mice and women : aspects of female aggression - Bjorkqvist, Kaj; Niemela, Pirkko (Academic Press, Inc., Harcourt Brace Jovanovich, Publishers, 1992)
This book is a comprehensive compilation and discussion of research findings on female aggression from anthropology, social psychology, animal research, case studies, and representations in literature. This multidisciplinary approach will address such questions as: 'Are females less aggressive than males?' 'Is female aggressive behavior perhaps quantitatively, different than male aggressive behavior?' The book also discusses patterns of agression, the role of hormones in aggression, cultural differences, and how human aggression differs from aggression within animal species.